Self-awareness as an important factor in optimizing first-year students to learning activities - Demchenko, V. (New Collegium, 2021)
In modern conditions, when the process of integration of Ukrainian higher education into the European system takes place, and this is associated with improving the quality of training, of particular importance is the psychological adaptation of freshmen to the new conditions of learning. Adaptation of freshmen to the new conditions of higher education is associated with increased activity of the individual, with the formation of his new qualities, with a different attitude to the new world, and self-awareness in this world. Thus, this process will be successful if the student in the initial period of study can quickly and correctly understand the new requirements of learning, acquire the knowledge and skills necessary to function in a student environment, as well as hi focuses on the necessary values of his future professional and social activities. With the development of self-awareness, as a result of self-knowledge, during communication and activity, it appeares a self-concept in a person, which gradually improves and becomes an important structural element of his psychological state. Scientists distinguish two types of I-concept: positive and negative. Positive self-concept is regarded as positive attitude towards oneself, self-esteem, self-acceptance, and negative – as negative attitude towards oneself, rejection of oneself, feelings of inferiority. At discrepancy between a real situation and personal ideals various emotional reactions are possible. Differences between the real and the ideal, as well as between the real and the appropriate give rise to qualitatively different types of impaired adaptation of the individual to the conditions of activity. Self-awareness plays a significant role in the process of psychological adaptation of freshmen in the early stages of learning. And the correspondence of the real self to the ideal self, which forms a positive self-concept, is one of the important factors that help to optimize the process of adaptation of freshmen to study in higher educational institution.